The Soul experience - Television Syndications, Inc.; U.S.A. Home Video ([s.l.] : U.S.A. Home Video, 1984)
The greatest names in soul music from the 60's and 70's are brought together in one electrifying video event.
Love me or let me be lonely / The Friends of Distinction -- Are you ready / Pacific Gas and Electric -- 25 miles / Edwin Starr -- Want adds / Honey Cone -- Ain't no sunshine / Bill Withers -- My sweet lord / Billy Preston -- I gotcha / Joe Tex -- Mr. big stuff / Jean Knight -- Tears of a clown / Smokey Robinson and the Miracles -- Natural man / Lou Rawls -- Respect yourself/I'll take you there / The Staple Singers -- Shake me wake me / The Four Tops --Let's stay together / Al Green -- Troglodyte / The Jimmy Castor Bunch -- Push and pull / Rufus Thomas -- Jesus is just alright / Ronnie Dyson -- If there's hell down below / Curtis Mayfield -- Valley of the dolls / Dionne Warwick -- Outa space / Billy Preston -- Wade in the water / Pacific Gas and Electric -- I can see clearly now / Johnny Nash -- We the people / The Staple Singers.
VHS format.
"212-343"
Videocassette release of the 1984 program by Television Syndications, Inc.
The Friends of Distinction, Pacific Gas and Electric, Edwin Starr, Honey Cone, Bill Withers, Billy Preston, Joe Tex, Jean Knight, Smokey Robinson and the Miracles, Lou Rawls, The Staple Singers, The Four Tops, Al Green, The Jimmy Castor Bunch, Rufus Thomas, Ronnie Dyson, Curtis Mayfield, Dionne Warwick, Billy Preston, Johnny Nash.
Keywords: Soul music